Особливості імпресіонізму на прикладах творів Берти Морізо - Бухарова, Л. Д. (ХНУРЕ, 2021)
The given work is devoted to the development of the European art in women’s artwork in various directions, in particular, study of the prominent French artist Berthe Morisot as the outstanding representative of The Impressionism in the late 19th century.
Keywords: імпресіонізм; українознавство